Development of a relational database management system - Ruiz, Anabel Natalia (2003)
The studies of Relational Data Base Management Systems and Databases constitute nowadays a main tren of investigation in large businesses and universities of the entire world. The creation of a data base engine keeps being a challenge since there are aspects in which have not been achieved a final solution. Por example, the requeriments of storage of images, video, sound. etc. The purpuse of this project is to implement a Relational Database Manager System (RDBMS) and an Interpreter of Data Query Language that can be utilized in investigation an data processing development of applications. It is important to count on a RDBMS developed in our universities so they can study an do modifications, which is practically impossible with the commercial products due to that does not available neither their Source code neither the documentation detailed neither the necessary training. Our investigation includes the development of innovating algorithms for access and maintenance of the data and procedures; techniques and tools to carry out Datawarehouse and DataMining, offering a good fulfillment as for time of answer and extensive capacity of backup to requeriments such as operational as strategic (Decision Support Systems).